NORMATIVITAS KEILMUAN HUKUM DALAM PERSPEKTIF ALIRAN PEMIKIRAN NEO-KANTIAN - FX. Adji Samekto (Faculty of Law, Universitas Diponegoro, 2015)
Scientific normativity of law conceived as a character inherent in legal science as a sui generis. Jurisprudence basically study the law, something that initially emerged from the dogmatic belief in philosophy. Dogmaticism refuse to alter beliefs one iota. The teachings of dogmatic philosophy stems from the teachings of Plato (428-347 BC) and is reflected in the legal enforceability. Dogmaticism in the law is reflected in the Corpus Juris Civilis. Along with the development of post Era Scholastic philosophical thinking, the philosophy synthesizes thought between dogmatic thinking and skeptic has appeared in the Age of Enlightment.This idea is reflected in Transcendental Idealist philosophy thought of Immanuel Kant (1724 to 1804). The core idea is that real human beings are given the ability tounderstand based on empirical experience and actually also able to gain an understanding of the human being that is the essence of symptoms. Transcendental Idealist, thus dynamic, moving to look for values that are useful for life. Transcendental Idealist thought then be adopted Kelsen (18811973) in the teaching of normativity in legal positivism (legal positivism). Normativity in the teachings of Hans Kelsen’s legal positivismderived from the integration of empirical positivism and idealistic positivism.Keywords : Normativity, Neo-kantian, Hans Kelsen, Transsendental IdealisNormativitas keilmuan hukum dikonsepsikan sebagai karakter yang melekat pada keilmuan hukum sebagai cabang ilmu yang bersifat sui generis.Disebut demikian karena ilmu hukum pada dasarnya mempelajari hukum, sesuatu yang pada awalnya dimunculkan dari pemikiran filsafat yang beraliran dogmatik. Pemikiran filsafat dogmatik menolak alternatif keyakinan (belief) lain dalam berpikir. Pemikiran filsafat dogmatik bermula dari ajaran Plato (428-347 SM) dan tercermin dalam keberlakuanhukum. Dogmatika dalam hukum sangat tercermin dalam Corpus Juris Civilis. Seiring dengan perkembangan pemikiran filsafat pasca Era Skolastik, maka pemikiran filsafat yang mensintesakan antara pemikiran dogmatik dan skeptik telah muncul di Era Pencerahan.Pemikiran tercermin dari filsafat pemikiran Transendental Idealis dari Immanuel Kant (1724-1804). Inti pemikirannya adalah bahwa manusia sesungguhnya diberi kemampuan untuk memahami berdasarkan pengalaman empirisdan sesungguhnya pula manusia mampu mendapat pengertian tentang gejala yang bersifat esensi. Transendental Idealis, dengan demikian bersifat dinamis, bergerak untuk mencari nilai-nilai yang berguna untuk kehidupan. Pemikiran Transendental Idealis inilah yang kemudian menjadi landasan pemikiran Hans Kelsen (1881-1973) dalam mengajarkan normativitas dalam positivisme hukum (legal positivism). Normativitas dalam positivisme hukum ajaran Hans Kelsen bersumber dari integrasipositivisme empiris dan empirisme idealis.Kata Kunci : Normativitas, Neo-kantian, Hans Kelsen, Transsendental Idealis